Recent Publications (Quarterly Journal of Economics, 1937)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 51, Issue 3, May 1937, Pages 551–555, https://doi.org/10.1093/qje/51.3.551 Published: 01 May 1937